2015
DOI: 10.1161/hypertensionaha.114.04373
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Kv7 Channels to Natriuretic Peptide Mediated Vasodilation in Normal and Hypertensive Rats

Abstract: The Kv7 family of voltage-gated potassium channels are expressed within the vasculature where they are key regulators of vascular tone and mediate cAMP-linked endogenous vasodilator responses, a pathway that is compromised in hypertension. However, the role of Kv7 channels in non–cAMP-linked vasodilator pathways has not been investigated. Natriuretic peptides are potent vasodilators, which operate primarily through the activation of a cGMP-dependent signaling pathway. This study investigated the putative role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
71
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(77 citation statements)
references
References 25 publications
(23 reference statements)
6
71
0
Order By: Relevance
“…31) Marrachelli et al 26) found that the impaired ANP-induced relaxation in the renal artery of diabetic rabbits was at least partly due to the impaired participation of K ATP , K v , and K Ca channels. Recently, Stott et al 50) observed that the ANP-induced vasodilation was mediated by K v 7 channels in the rat aorta and renal artery, and suggested that the reduced ANP-induced vasodilation in such arteries of SHR was attributable to impaired K v 7 activity. In the present study, ANP-induced relaxation was altered by neither 4-AP (K v inhibitior) nor glibenclamide (K ATP inhibitor) in carotid arteries from both SHR and WKY.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…31) Marrachelli et al 26) found that the impaired ANP-induced relaxation in the renal artery of diabetic rabbits was at least partly due to the impaired participation of K ATP , K v , and K Ca channels. Recently, Stott et al 50) observed that the ANP-induced vasodilation was mediated by K v 7 channels in the rat aorta and renal artery, and suggested that the reduced ANP-induced vasodilation in such arteries of SHR was attributable to impaired K v 7 activity. In the present study, ANP-induced relaxation was altered by neither 4-AP (K v inhibitior) nor glibenclamide (K ATP inhibitor) in carotid arteries from both SHR and WKY.…”
Section: Discussionmentioning
confidence: 99%
“…Relaxation responses are shown as a percentage of the PE-induced pre-contraction. For the functional studies, individual concentration-response curves were analyzed using a nonlinear regression curve fitting relaxation-drug concentration relationships to determine E max (the maximal response generated by the relaxant drugs), pD 2 (a negative logarithm of EC 50 which is the concentration of the agonist producing 50% of E max ), and area under the curve (AUC), using Graph Pad Prism software (ver. 5.0 for Mac, San Diego, CA, U.S.A.).…”
Section: )mentioning
confidence: 99%
“…Renal artery segments (∼2 mm) were mounted in a myograph (Danish Myo Technology) for isometric tension recording (13). The chambers contained physiological salt solution, maintained at 37°C and aerated with 95% O 2 /5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…There are five Kv7 isoforms (Kv7.1-Kv7.5) of which Kv7.1, Kv7.4, and Kv7.5 are consistently expressed within VSM, where the predominant molecular architecture is a Kv7.4/Kv7.5 heterotetramer (2,3). Activation of Kv7 channels produces relaxation of numerous arteries (4)(5)(6)(7)(8), whereas blockade of Kv7 channels results in contraction of vessels at rest (7,(9)(10)(11) or an inhibition of endogenously derived vasorelaxations (2,(11)(12)(13). In addition, molecular reduction of Kv7.4 reduces responses to various Gs-coupled vasodilators in a number of arteries (2,11).…”
mentioning
confidence: 99%
“…The recent findings published in Stott et al 7 reveal that Kv7 channels are involved in mediating cyclic GMP (cGMP) dependent relaxations in the rat vasculature. The guanylate cyclase cGMP signaling pathway is a key vasodilator pathway involved in the regulation of vascular smooth muscle contractility.…”
mentioning
confidence: 99%